Neurological manifestations of malaria - Gustavo C. Román; Nimal Senanayake (Arquivos de Neuro-Psiquiatria)
The involvement of the nervous system in malaria is reviewed in this paper. Cerebral malaria, the acute encephalopathy which complicates exclusively the infection by Plasmodium falciparum commonly affects children and adolescents in hyperendemic areas. Plugging of cerebral capillaries and venules by clumped, parasitized red cells causing sludging in the capillary circulation is one hypothesis to explain its pathogenesis. The other is a humoral hypothesis which proposes nonspecific, immune-mediated, inflammatory responses with release of vasoactive substances capable of producing endothelial damage and alterations of permeability. Cerebral malaria has a mortality rate up to 50%, and also a considerable longterm morbidity, particularly in children. Hypoglycemia, largely in patients treated with quinine, may complicate the cerebral symptomatology. Other central nervous manifestations of malaria include intracranial hemorrhage, cerebral arterial occlusion, and transient extrapyramidal and neuropsychiiatric manifestations. A self-limiting, isolated cerebellar ataxia, presumably caused by immunological mechanisms, in patients recovering from falciparum malaria has been recognized in Sri Lanka. Malaria is a common cause of febrile seizures in the tropics, and it also contributes to the development of epilepsy in later life. Several reports of spinal cord and peripheral nerve involvement are also available. A transient muscle paralysis resembling periodic paralysis during febrile episodes of malaria has been described in some patients. The pathogenesis of these neurological manifestations remains unexplored, but offers excellent perspectives for research at a clinical as well as experimental level.